CONSUMER AWARENESS AND PROCESSING MECHANISMS TOWARDS AFFILIATE MARKETING IN CHENNAI DISTRICT - S.V.Divya; D.Jansi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With the rapid growth of online platforms and increase in the internet penetration, affiliate marketing has transformed over time. The digital transformation has ushered in an era where every products and services are just a click away. Additionally, the products and services have become easily accessible 24/7, which has immensely supported this particular strategy. Similar to the commission-based sales, this marketing strategy is currently on the vogue due to the growth of social media and its users. Moreover, the increase in the micro and macro influencers promoting products and services online has significantly contributed to its growth. Affiliate marketing is gaining momentum in fashion, technology, finance, education and travel. It is also considered as a cost-effective way to promote a product or service as affiliates are paid only when a sale is made. Thus with innumerable benefits to offer, affiliate marketing is becoming the most sought after strategy in the modern digital landscape. Against this backdrop, the present study has been taken up to analyse the consumer awareness and processing mechanisms towards affiliate marketing. The present study has employed a well structured questionnaire to collect the required data. A sample of 483 was contacted on the basis of purposive sampling. Weighted average score, Kruskal Wallis test and Mann Whitney U test have been used to analyse the collected data.